Revalence of ixodid ticks in buffaloes of Indore district, Madhya Pradesh, India - Kumar Mandloi, Umesh; Jayraw, Anantrao Kashiram; Prasad Jatav, Gaya; Shakya, Mukesh; Agrawal, Vivek; Jamra, Nirmala (Buffalo Bulletin, 2024)
Ticks which are highly prevalent in tropical and subtropical regions, top the list as arthropod vectors amongst microbial diseases in non-human vertebrates and are major constraint in achieving maximum production from buffaloes which are commonly called as ‘Black Diamond’ owing to their versatile role in the socioeconomic upliftment. Although voluminous literature is available pertaining to prevalence of ticks in cattle, but when it comes to buffaloes, very scanty literature is available about buffalo ticks. Therefore, an investigation was carried out to assess the prevalence of ixodid ticks in buffaloes of Indore district. Every month, ticks were collected from a total of 9922 buffaloes belonging to randomly selected 5 villages of each tehsil of Indore district, viz. Indore, Mhow, Depalpur, Sanwer and Hatod. The current study revealed an overall tick prevalence of 42.49% with significantly high prevalence of Rhipicephalus microplus (29.83%) than Hyalomma anatolicum (10.14%) and mixed infestation (2.52%). Month-wise, the tick prevalence was significantly high in the month of September (48.41%) while it was significantly lowt in the month of January (30.04%). Season-wise, the prevalence of ticks was highest in monsoon (48.41%) than summer (42.55%) and winter (40.75%). Amongst the various age groups, significantly high tick infestation was evident in 1–3-year-old (71.35%) than <1 year-old (49.29%) and >3-year-old (37.47%) animals. Significantly high prevalence was recorded in males (59.47%) than that of females (41.09%). Significantly higher rate of occurrence was noted in Mhow tehsil (50.49%) as compared to Depalpur (43.76%), Indore (43.35%), Sanwer (38.42%) and Hatod (36.53%) tehsils of Indore district.